The antecedent of SME performance and the effect of government support in Nigeria - Ibrahim, Maryam Imam (2018)
Small and medium enterprises (SMEs) play a vital role in both developed and developing nations. In Nigeria, SMEs have been recognised for their valuable contribution to the nation's economy. Despite the relevance and importance of SMEs, much of the literature indicates there are very few studies that attempted to investigate the factors -which influence SMEs' performance in Nigeria, particularly the role of government support policies (GSPs) on SMEs performance. Thus, the objective of this study is to examine the relationship between entrepreneurial orientation (EO), technology orientation (TO) and contemporary marketing (CM) on SMEs performance in Nigeria with a moderating role of GSPs. This study employed a cross-sectional design using questionnaires, data were collected from SMEs owner-managers. The study was based on stratified sampling and 240 SMEs were randomly selected. Questionnaires were distributed and collected through personally-administered method and Partial Least Squares Structural Equation Modelling was used to test the hypotheses. The results indicated TO and CM as having a positive effect on SMEs performance. Similarly, GSPs /moderate the relationship between EO and TO on the SMEs' performance. However, the relationship between EO and SMEs' performance was not supported in this study. Furthermore, GSPs do not have a significant influence on CM and SMEs' performance. The findings of this study offer important insights to regulators/policy-makers of SMEs, SMEs owner-managers, and researchers to further understand the effects of these strategic variables. Owner-mangers of SM Es should accentuate on these variables. However, over-emphasis on EO may affect firms in a negative way which results in poor performance. Policy-makers should support SMEs owner-managers in the areas of training and capacity building. Lastly, limitations of the current study suggest opportunities for researchers interested in exploring other determinates of SMEs performance.